LANGUAGE, POWER, AND EMOTIONAL CONTROL IN GEORGE ORWELL’S 1984 - Shodiyeva Ruxshona, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract:  In this article, George Orwell’s 1984 describes a dystopian society in which language functions as a central instrument of power, psychological control, and emotional domination. Through the fictional language Newspeak, the Party systematically restricts vocabulary to eliminate subversive thoughts and reshape cognition, illustrating how totalitarian regimes can harness linguistic structures to limit intellectual freedom and emotional autonomy. This article examines the mechanisms by which language structures and enforces power, the role of emotion and psychological conditioning in control, and the broader implications of Orwell’s critique for understanding language and authority in real political contexts.